2021
DOI: 10.1155/2021/1815178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Incretin-Based Medications on Lipid Metabolism

Abstract: Pathophysiological pathways that are induced by chronic hyperglycemia negatively impact lipid metabolism. Thus, diabetes is commonly accompanied by varying degrees of dyslipidemia which is itself a major risk factor for further macro- and microvascular diabetes complications such as atherosclerosis and nephropathy. Therefore, normalizing lipid metabolism is an attractive goal for therapy in patients with diabetes. Incretin-based medications are a novel group of antidiabetic agents with potent hypoglycemic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…[2][3][4][5][6][7][8] Since their introduction, several different formulations of these antidiabetic agents have been brought to market; to date, seven injectable analogues (twicedaily exenatide immediate-release, once-weekly exenatide extendedrelease, once-daily liraglutide, once-daily lixisenatide, once-weekly albiglutide [currently off-market due to a decline in sales], onceweekly dulaglutide and once-weekly semaglutide) and one orallyadministered analogue (once-daily semaglutide) have been approved by the Food and Drug Administration (FDA). 9 Besides GLP-1 receptor as their putative target, numerous molecular targets have been identified for GLP-1 RAs, [10][11][12][13][14][15][16][17][18][19] which justifies their potential for wider medical applications. In this context, several studies have demonstrated that GLP-1 RAs can alter serum uric acid (SUA) concentration.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Since their introduction, several different formulations of these antidiabetic agents have been brought to market; to date, seven injectable analogues (twicedaily exenatide immediate-release, once-weekly exenatide extendedrelease, once-daily liraglutide, once-daily lixisenatide, once-weekly albiglutide [currently off-market due to a decline in sales], onceweekly dulaglutide and once-weekly semaglutide) and one orallyadministered analogue (once-daily semaglutide) have been approved by the Food and Drug Administration (FDA). 9 Besides GLP-1 receptor as their putative target, numerous molecular targets have been identified for GLP-1 RAs, [10][11][12][13][14][15][16][17][18][19] which justifies their potential for wider medical applications. In this context, several studies have demonstrated that GLP-1 RAs can alter serum uric acid (SUA) concentration.…”
mentioning
confidence: 99%
“…Current literature highlights the importance of lipids on the function of GPCRs, with cholesterol playing a direct role as a potential allosteric modulator as well as an indirect effect related to the segregation of these receptors to cholesterol-rich nanodomains in the plasma membrane. While most of the work done regarding lipids and the glucagon receptor family has revolved around incretin receptor regulation of lipid metabolism ( Yaribeygi et al . 2021 ), there is currently sparse information about the regulation of GLP-1R and GLP-2R by lipids, and little to no information about the regulation of GIPR, either directly or indirectly due to lipid modification of GIPR agonists.…”
Section: Conclusion and Prospective Future Workmentioning
confidence: 99%
“…Incretins are hormones released by the enteroendocrine L-cells of the gastrointestinal (GI) tract in response to food intake [38] . They stimulate the release of insulin from the pancreas and reduce the production of glucagon, helping to normalize postprandial glucose levels [38] , [39] . Incretin-based medications mimic the actions of natural incretins, such as GLP-1 and gastric inhibitory hormone (GIP).…”
Section: Glp-1 Receptor Agonists and Semaglutidementioning
confidence: 99%